Numerical simulation of an oil droplet passing through an EHL contact. (August 2017) - Li, S.Y.; Guo, F.; Li, X.M.; Liu, C.L.
Abstract: In oil-air lubrication lubricants are supplied by droplets to tribo-pairs. Numerical work has been carried out to investigate transient EHL film when an oil droplet is entrained. Results show that entrainment speed, oil viscosity and wettability of the oil/solid interface significantly affect the lubricant side flow across the entrainment direction (termed as squeeze spread) at the inlet, and consequently different EHL behaviors are presented. For fast speeds, high oil viscosity and low wettability, when a small droplet passes through the central contact a dimple-shaped film is generated and bounding surfaces cannot be fully separated. Numerical results showed close correlation to the experiments. This study is beneficial to basic understanding of lubrication by limited lubricant supply. Highlights: An EHL model with entraining an oil droplet was proposed and numerical results have been obtained for parametric study. For fast entrainment speeds, high oil viscosity and low wettability, a dimple-shaped EHL film is generated. Numerical results show that the lubricant side flow across the entrainment direction at the inlet dominates the film shape.